Phase relations of the (Pr1−xSmx)2Fe14B system. (3rd April 2017) - Xu, Chengfu; Chen, Kanghua; Gu, Zhengfei; Ma, Dongdong; Cheng, Linyi; Cheng, Gang; Rao, Guanghui
ABSTRACT: The phase relations in the (Pr1− x Sm x )2 Fe14 B system in a whole concentration range have been studied by means of X-ray powder diffraction (XRD), differential thermal analysis (DTA) and scanning electron microscopy (SEM) equipped with energy-dispersive X-ray spectroscopy (EDS). The XRD patterns of the (Pr1− x Sm x )2 Fe14 B samples have been refined by Rietveld method. These results reveal that all the alloys (Pr1− x Sm x )2 Fe14 B are similar to the end member of the investigated system Pr2 Fe14 B with tetragonal structure (space group P42 /mnm). The continuous solid solutions were formed in this system. The normalized lattice parameters and unit cell volumes of (Pr1− x Sm x )2 Fe14 B solid solutions decrease linearly with x ranging from 0 to 1.0. The DTA measurements show that the peritectic temperature of (Pr1− x Sm x )2 Fe14 B increases with increasing Sm content and no metastable phases are detected. Based on the DTA data, SEM–EDS and XRD results, the vertical section of Pr2 Fe14 B– Sm2 Fe14 B in the Pr–Sm–Fe–B system has been constructed.